Absolute Lymphocyte Count Is Not a Suitable Alternative to CD4 Count for Determining Initiation of Antiretroviral Therapy in Fiji. (23rd October 2014) - Balak, Dashika A.; Bissell, Karen; Roseveare, Christine; Ram, Sharan; Devi, Rachel R.; Graham, Stephen M.
Abstract : Introduction . An absolute lymphocyte count is commonly used as an alternative to a CD4 count to determine initiation of antiretroviral therapy for HIV-infected individuals in Fiji when a CD4 count is unavailable. Methods . We conducted a retrospective analysis of laboratory results of HIV-infected individuals registered at all HIV clinics in Fiji. Results . Paired absolute lymphocyte and CD4 counts were available for 101 HIV-infected individuals, and 96% had a CD4 count of ≤500 cells/mm 3 . Correlation between the counts in individuals was poor (Spearman rank correlationr = 0.5 ). No absolute lymphocyte count could be determined in this population as a suitable surrogate for a CD4 count of either 350 cells/mm 3 or 500 cells/mm 3 . The currently used absolute lymphocyte count of ≤2300 cells/ μ L had a positive predictive value of 87% but a negative predictive value of only 17% for a CD4 of ≤350 cells/mm 3 and if used as a surrogate for a CD4 of ≤500 cells/mm 3 it would result in all HIV-infected individuals receiving ART including those not yet eligible. Weight, CD4 count, and absolute lymphocyte count increased significantly at 3 months following ART initiation. Conclusions . Our findings do not support the use of absolute lymphocyte count to determine antiretroviral therapy initiation in Fiji.